Forestry and climate change (CABI, 2007)
This book contains 28 chapters grouped into six sections providing information on forests interact with the other components of the physical and natural world with the human society, and how we could manage forests globally to make the most of their contribution to mitigation of climate change along with the established objective of sustainable management to maximize the full range of economic and non-market benefits which forests provide. Topics covered include: introduction on the interaction between forests and climate change; climate change, forestry and science-policy interface; forestry options for contributing to climate change mitigation; options for adaptation due to impacts of climate change on forests; current and future policy of national and international frameworks; and implications for future forestry and related environmental and development policy.